Keragaman Sifat Fisik Padi Lokal di Desa Ture, Jambi - Wahyudhi, Aditya; Herawani, Febrina; Tirto, Muhammad; Rif'atunidaudina, Ria; Theodora, Theodora; Mastura, Siti; Mora, Andita Minda; Rahmawati, Noni; Aidiah, Aidiah; Nasrudin, Nasrudin (Universitas Lampung, 2024)
Local rice is a very important germplasm in the plant breeding program of superior rice. Jambi is one of the provinces in Indonesia which has a high diversity of local rice. This high diversity includes the diversity of physical characters of the shape and size of grain. This study aims to look at the physical diversity of lokal Jambi rice grains found in Ture Village. Research on the diversity of physical characters of Jambi local rice was conducted in Ture Village, Pemayung District, Batanghari Regency, Jambi Province. The local rice observed were Putih, Layap, Sereh wangi, Sekempol, Putih Kuning, Jarum Mas, Nak Daro and Ketan Hitam. The physical characters of grain that were observed were grain length, grain width, grain shape, rice color. The results showed that Sekepol was a short type of rice, Ketan Hitam and Jarum Mas were a long rice and the other cultivars were a medium type. Based on the shape of the rice, the Sereh wangi, Jarum Mas and Ketan hitam have a slender shape while the other cultivars are oval. The color of Ketan hitam is red and the other cultivars are white. Keywords : germplasm; local rice; physical characters; grain shape